Korelasi Kompetensi Kepala Sekolah dengan Kinerja Guru Sekolah Dasar - Sari Nusantara Putri (Pusat Pengembangan Pendidikan dan Bakat Indonesia, 2022)
The ability of the principal in managing the school becomes a reference in the success of the learning process in the school in managing every component in the school. Teachers are professional educators with their main tasks being to educate, teach, guide, direct, assess, and evaluate learners. This study examined the competence of the principal related to the performance of teachers. This research aims to find out the correlation of the competence of the principal with teacher performance. The study used correlational quantitative methods and data collected using the principal's competency questionnaire sheet and the Teacher's performance observation sheet. The results showed a significant correlation between the competence of the principal and the performance of teachers with a contribution of 53%. The description shows that the hypothesis that the author formulated was accepted to be true. Thus it can be concluded that there is a correlation of the competence of the principal with teacher performance. If the competence of the principal is realized in accordance with dimensions and tupoksi then the teacher's performance will certainly be better.